The Duquesne Christmas mystery - Stevens, Thomas Wood, 1880-1942; Gage, Harry Lawrence, 1887-1982 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Duquesne Christmas mystery by Thomas Wood Stevens" is a religious pageant or dramatic play written in the early 20th century. The book presents a dramatized retelling of the Nativity story, focusing on the birth of Christ as prophesied by the prophets and witnessed by shepherds, the Magi, and the people of Bethlehem. It combines elements of biblical prophecy, dramatic dialogue, and staged spectacle, likely intended for community or church performance around Christmastime. The story opens with ancient prophets$1 (BIsaiah, Micah, and Hosea$1 (Bproclaiming the coming of the Messiah as foretold in scripture. It then follows the journey of three Eastern Kings (the Magi) who, guided by a star, arrive in search of the newborn King. Along the way, their encounter with the suspicious and malevolent King Herod sets the stage for the looming threat to the child. Meanwhile, shepherds receive a heavenly message from Gabriel and are called to witness the birth. The narrative culminates in a vision of the Nativity, with Mary and the infant Jesus in the manger, visited by shepherds and kings, and ultimately joined by the diverse people of the city in joyful celebration. The play concludes with a symbolic community gathering around a lit Christmas tree, signifying hope and unity. (This is an automatically generated summary.)s
Release date is 2025-04-28
Carol Brown, Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Christmas plays